Prevalence of caseous lymphadenitis in goats in Peninsular Malaysia - Bahaman, Abdul Rani; A. E, Maznah; M. S, Hajariah; Azhar, P. Z. (Veterinary Association Malaysia, 1989)
In a cross-sectional study of 3484 goats from intensive farms and smallholdings throughout Peninsular Malaysia, 242 of the aniamls examined had evidence of caseous lymphadenitis (CLA) as disclosed by the gel diffusion test. High prevalence of infection was indicated in the semi-intensive farms whilst infection was evidenced in smallholdings from only two localities. The gel diffusion test used in this study to detect antitoxin to Corynebacterium pseudotuberculosis exotoxin in the test serum samples was seen as a simple method of screening animals for CLA